(untitled) (Harmoni, 2020)
Nowadays the tolerance of community life in Kupang City, East Nusa Tenggara Province has been going well. One form of tolerance is reflected in the construction of six houses of worship for adherents of six religions is called the tolerance village in Kelurahan Naibonat, Kupang Timur District. This indicates that the city of Kupang is a city that is friendly to diversity. The role of the community, especially Hindus and Christians in maintaining the tolerance of community life begins with the concept of unity and the motto of the City of Kupang, KASIH (Kupang, Safe, Healthy, Beautiful and Harmonious) which is the background of the realization of community life tolerance in Kupang City, East Nusa Tenggara. The method used is a qualitative research method using a sociological approach. Data collection in this study includes various activities such as: observation, interviews, then data analysis and make recommendations from the results of research conducted. Determination of respondents is done by using purposive sampling technique. In addition to getting a more comprehensive, clear and complete data picture, the researcher uses library research as a method of collecting data to complete the results and search for literature relevant to the object of research. The results of this study found several supporting factors in maintaining the tolerance of community life in Kupang City including: (1) Geneologists, (2)Role of Religious Leaders, (3) Socially Awareness Communities and (4) Role of Places of Worship. The various forms of participation of the two people, both Hindu and Christian, are shown by: (1) Mutual assistance in maintaining security and order in Kupang City during religious festivals, (2) Improving hospitality, (3) Mutual cooperation and (4) Cooperation of education in strengthening the concept of unity to prevent provocation, radicalism and SARA seeds from entering and destroying the lives of people in Kupang City.